2021
DOI: 10.3390/ma14195735
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Electronics to Textiles by Ultrasonic Welding for Cable-Driven Applications for Smart Textiles

Abstract: The connection between flexible textiles and stiff electronic components has always been structurally weak and a limiting factor in the establishment of smart textiles in our everyday life. This paper focuses on the formation of reliable connections between conductive textiles and conventional litz wires using ultrasonic welding. The paper offers a promising approach to solving this problem. The electrical and mechanical performance of the samples were investigated after 15 and 30 wash-and-dry cycles in a laun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…24 The latest publications describe the investigations into ultrasonic spot welding as a technology for connecting textile-integrated conductors. 25,26 It was also recently reported that electronic modules can be electrically and mechanically integrated on textile-based circuit boards by means of ultrasonic plastic welding. 27 This research focuses on the realization of stable, low-resistance electrical contacts between crossing hybrid conductive yarns by ultrasonic spot welding.…”
mentioning
confidence: 99%
“…24 The latest publications describe the investigations into ultrasonic spot welding as a technology for connecting textile-integrated conductors. 25,26 It was also recently reported that electronic modules can be electrically and mechanically integrated on textile-based circuit boards by means of ultrasonic plastic welding. 27 This research focuses on the realization of stable, low-resistance electrical contacts between crossing hybrid conductive yarns by ultrasonic spot welding.…”
mentioning
confidence: 99%
“…Such connections have been typically achieved by using soldering/welding or mechanical gripping of fiber electrodes. However, the soldering/welding of multiple fiber electrodes may lead to a rigid textile network, decreasing their comfortability as wearable devices. , In addition, the brittle connections of the textile network, formed by either soldering/welding or mechanical gripping, may not survive repeated mechanical deformations, resulting in device failures. Further, integrating multiple fiber devices increases the difficulty in large-scale fabrication.…”
Section: Challenges For Fiber Devicesmentioning
confidence: 99%
“…Results showed that the higher temperatures at the welding interface in continuous ultrasonic welding are attributed to pre-heating of the energy director due to vibrations being transmitted downstream of the sonotrode. Micus et al [13] focused on the formation of reliable connections between conductive textiles and conventional litz wires using ultrasonic welding. It was found that the resistance of joints increased more than 300% because silver-coated wires suffered under laundry cycles.…”
Section: Introductionmentioning
confidence: 99%